Prevalence of sleep apnoea and capnographic detection of nocturnal hypoventilation in amyotrophic lateral sclerosis. Issue 4 (20th October 2017) - Boentert, Matthias; Glatz, Christian; Helmle, Cornelia; Okegwo, Angelika; Young, Peter
Abstract : Objective: This retrospective study aimed to investigate whether overnight oxymetry and early morning blood gas analysis predict nocturnal hypoventilation (NH) as reflected by night-time hypercapnia in patients with amyotrophic lateral sclerosis (ALS). In addition, prevalence and clinical determinants of sleep apnoea in ALS were evaluated. Methods: In 250 patients with non-ventilated ALS, transcutaneous capnometry was performed along with polysomnography or polygraphy and early morning blood gases. Results: 123 patients were female, and 84 patients had bulbar-onset ALS. 40.0% showed NH, and an apnoea–hypopnoea index (AHI) >5/hour was found in 45.6%. In 22.3%, sleep apnoea and NH coincided. The obstructive apnoea index was significantly higher than the central apnoea index (p<0.0001). Both NH and sleep apnoea were significantly more common in male than in female patients. Sleep apnoea and AHI were associated with better bulbar function. Desaturation time (t<90% ) and transcutaneous CO2 were negatively correlated with upright vital capacity. Early morning base excess (EMBE), bicarbonate and t<90% were independent predictors of NH. However, among 100 patients with NH, 31 were missed by t<90% >5 min and 17 were not identified when EMBE >3 mmol/L and t<90% >5 min were combined. Conclusion: In ALS, sleep apnoea is common and often accompanies NH. It is mainly obstructive, and central apnoea appears to be clinically irrelevant. Polygraphy or oxymetry alone are not sufficient to uncover NH. Combination of EMBE and t<90% may increase sensitivity, but transcutaneous capnography is strongly recommended for reliable detection of NH in patients with ALS.